2014
DOI: 10.15274/inr-2014-10050
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Superselective Angiography of Pediatric Moyamoya Disease Angioarchitecture: The Anterior Circulation

Abstract: The angioarchitecture of the so-called moyamoya vessels in children has not been explicitly analyzed. We aimed to investigate the precise anatomy of the vascular anastomotic networks in patients with childhood moyamoya disease. Six children diagnosed with moyamoya disease for the first time underwent an angiographic investigation with selective and superselective injections. We recorded the arterial branches feeding the moyamoya anastomotic networks, their connections and the recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nevertheless, collateral vessels in MMA have a very complex angioarchitecture and are difficult to investigate, even with superselective DSA. Recently, Baltsavias et al [32][33][34] first and precisely demonstrated the collateral circulations in pediatric Moyamoya disease by superselective DSA with microcatheters. However, superselective DSA is accompanied by considerable risks for cerebral hemorrhage because of vessels that might be injured by the microcatheter, especially in fragile Moyamoya collaterals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, collateral vessels in MMA have a very complex angioarchitecture and are difficult to investigate, even with superselective DSA. Recently, Baltsavias et al [32][33][34] first and precisely demonstrated the collateral circulations in pediatric Moyamoya disease by superselective DSA with microcatheters. However, superselective DSA is accompanied by considerable risks for cerebral hemorrhage because of vessels that might be injured by the microcatheter, especially in fragile Moyamoya collaterals.…”
Section: Discussionmentioning
confidence: 99%
“…Image evaluation was performed using a freeware DICOM reader (Horos, Version 2.0.1; http://www.horosproject.org/). DSCNs were classified according to location and connecting vessels, referring to morphologic characteristics described by Baltsavias et al, [32][33][34] who described collateral circulation in pediatric Moyamoya disease with superselective angiography. Images were analyzed by 1 experienced vascular neurologist (M.K.…”
Section: Image Analysismentioning
confidence: 99%